Hak Kekayaan Intelektual atas Pengetahuan Tradisional - Sulasi Rongiyati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2011)
Indonesia as a developing country that is rich in natural resources, arts, and culture have a variety of traditional knowledge. Its requires recognition and legal protection that is able to take care of ownership of traditional knowledge, as the creation of a nation that gained internationally recognition. Regulation in the intellectual property right, especially patent act aims to provide legal protection for an invention and provide economic benefits for inventor. However the Patent Act, the adoption intellectual property rights of developed countries, in their implementation has not been able to give recognition and protection to traditional knowledge optimally. This is caused by differences between the concept of Paten act is an exclusive and individual with the traditional knowledge that has the characteristics of traditional, communal, and open. Public knowledge of intellectual property rights is still lacking and inadequate mastery of technology and low budget is also an obstacle to patent traditional knowledge.ABSTRAKIndonesia sebagai negara berkembang yang kaya akan sumber daya alam, seni, dan budaya memiliki berbagai pengetahuan tradisional yang memerlukan pengakuan dan pelindungan hukum yang mampu menjaga terpeliharanya kepemilikan pengetahuan tradisional tersebut sebagai karya bangsa yang diakui secara internasional. Regulasi di bidang HKI, khususnya UU Paten bertujuan memberikan perlindungan hukum atas suatu penemuan karya intelektual kepada penemunya dan memberikan keuntungan ekonomis atas hasil temuannya. Namun UU Paten yang mengadopsi HKI negara-negara maju dalam implementasinya belum mampu memberikan pengakuan dan perlindungan kepada pengetahuan tradisional secara optimal. Hal ini disebabkan oleh perbedaan konsep antara HKI yang eksklusif dan individual dengan pengetahuan tradisional yang memiliki karakteristik tradisional, komunal, dan terbuka. Minimnya pemahaman masyarakat terhadap HKI serta penguasaan teknologi yang belum memadai serta minimnya anggaran juga menjadi kendala untuk mematenkan pengetahuan tradisional.